The Global Challenge of Campylobacter: Antimicrobial Resistance and Emerging Intervention Strategies - Zubeiru Bukari; Toyin Emmanuel; Jude Woodward; Richard Ferguson; Martha Ezughara; Nikhil Darga; Bruno Silvester Lopes (Tropical Medicine and Infectious Disease)
Antimicrobial resistance (AMR) in Campylobacter species, particularly C. jejuni and C. coli, poses a significant public health threat. These bacteria, which are commonly found in livestock, poultry, companion animals, and wildlife, are the leading causes of foodborne illnesses, often transmitted through contaminated poultry. Extensive exposure to antibiotics in human and veterinary medicine creates selection pressure, driving resistance through mechanisms such as point mutations, horizontal gene transfer, and efflux pumps. Resistance to fluoroquinolones, macrolides, and tetracyclines complicates treatment and increases the risk of severe infections. Drug-resistant Campylobacter is transmitted to humans via contaminated food, water, and direct contact with animals, highlighting its zoonotic potential. Addressing this challenge requires effective interventions. Pre-harvest strategies like biosecurity and immune-based methods reduce bacterial loads on farms, while post-harvest measures, including carcass decontamination and freezing, limit contamination. Emerging approaches, such as bacteriocins and natural antimicrobials, offer chemical-free alternatives. Integrated, multidisciplinary interventions across the food chain are essential to mitigate AMR transmission and enhance food safety. Sustainable agricultural practices, antimicrobial stewardship, and innovative solutions are critical to curbing Campylobacter resistance and protecting global public health. Our review examines the dynamics of antimicrobial resistance in Campylobacter and presents current strategies to mitigate Campylobacter-related AMR, offering valuable insights for antimicrobial control in the poultry industry.